Soft Computing and Signal Processing Proceedings of 7th ICSCSP 2024, Volume 1 - Reddy, V. Sivakumar; Wang, Jiacun; Chetti, Prasad; Reddy, K. T. V. (Lecture Notes in Networks and Systems, 2025)
XXII, 713 p. 344 illus., 291 illus. in color.